2018
DOI: 10.1371/journal.pone.0192940
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial health and suicidal ideation among people living with HIV/AIDS: A cross-sectional study in Nanjing, China

Abstract: BackgroundSuicide is a serious cause of mortality worldwide and is considered as a psychiatric emergency. People living with HIV/AIDS (PLWHA) have higher rates of suicidal behavior than the general population. This study assessed the prevalence and verified the syndemic effect of psychosocial health conditions on suicidal ideation among PLWHA in China.MethodsAn institutional-based cross-sectional study was conducted from July to August 2016 in Nanjing, China, using a self-report questionnaire. Sociodemographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
80
9
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(99 citation statements)
references
References 69 publications
(87 reference statements)
6
80
9
4
Order By: Relevance
“…The present study also showed that the lower educational levels significantly predicted a higher adjusted odds ratio of suicide ideation. The previous studies also indicated that the lower education level was associated with higher occurrence rates of suicidal ideation and higher levels of depressive symptoms (Badiee et al., ; Eller et al., ; Wang et al., ).…”
Section: Discussionmentioning
confidence: 88%
“…The present study also showed that the lower educational levels significantly predicted a higher adjusted odds ratio of suicide ideation. The previous studies also indicated that the lower education level was associated with higher occurrence rates of suicidal ideation and higher levels of depressive symptoms (Badiee et al., ; Eller et al., ; Wang et al., ).…”
Section: Discussionmentioning
confidence: 88%
“…In China's mainstream culture this issue is a particular challenge. Some research has even considered STIs as a factor behind the syndemic effect on suicidal ideation, whereas the present study focused particularly on STI patients' psychosocial problems 29,30,33 . Only one study has discussed the association between a syndemic effect of psychosocial complements (depression, self-esteem, and social support) and suicidal ideation among HIV+ patients in Nanjing, China 29 .…”
mentioning
confidence: 97%
“…Notably, individuals with several psychosocial problems may have magnified suicidal ideation 4,28,29 .…”
mentioning
confidence: 99%
“…Another matter we realized is that these studies contain behavioral habits, risky sexual behaviors, unpleasant sexual experiences, and psychosocial conditions which involves privacy, are not easy to get true answers and do not apply to the mainstream culture of China. Furthermore, some research has even considered STIs as a factor of the syndemic effect on suicidal ideation, while our present study focused particularly on STI patients' psychosocial issues 28,[31][32] . Only one study has discussed the association between a syndemic effect of psychosocial complements (depression, self-esteem, and social support) and suicidal ideation among HIV+ patients; that was in Nanjing, China 32 .…”
mentioning
confidence: 99%
“…Furthermore, some research has even considered STIs as a factor of the syndemic effect on suicidal ideation, while our present study focused particularly on STI patients' psychosocial issues 28,[31][32] . Only one study has discussed the association between a syndemic effect of psychosocial complements (depression, self-esteem, and social support) and suicidal ideation among HIV+ patients; that was in Nanjing, China 32 . Among other populations is a study our team conducted that found the psychosocial syndemic effect (self-esteem, depression, social support, and loneliness) and suicidal ideation in men who have sex with men (MSM), also in China 29 .…”
mentioning
confidence: 99%